Comparative Evaluation of Clinical Performance of Three Different Glass Hybrid Restorations in High Caries Risk Patients: A Randomized Control Trial - Fattah, R. I. Abdel; Jamil, W. E.; Elezz, A. F. Abo (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Finding a restorative material that can survive and be quite resistant in high caries risk patients is very challenging, that’s why three different glass hybrid restorations were tested for their clinical performance for one year in high caries risk patients. AIM: This study was conducted to evaluate the clinical performance of three glass hybrid restorations; nano-ionomer restoration (Ketac Nano), bioactive ionomer glass fillers (Activa bioactive), and alkasite restorative material (Cention N) in Class I cavity in high caries risk patients after 1 year according to the FDI criteria for the assessment of dental restorations. METHODS AND MATERIALS: Fifteen cooperative patients, males or females with high caries risk who were approving to participate in the trial of age range 18–50 years, were selected in the present study. Every patient should have three or more posterior teeth having occlusal pits and fissure carious lesions. Three Class I cavities were performed for every patient and restored randomly with Ketac Nano™, Activa Bioactive™, and Cention N™. All three restorations were applied, according to the manufacturers’ instructions. Restorations were evaluated at baseline (immediately), after 3 months, 6 months, and 1 year by two blinded assessors using FDI criteria for the assessment of dental restorations measuring functional properties. STATISTICAL ANALYSIS USED: Evaluation of functional properties was checked by Kruskal–Wallis non-parametric test statistics at 0.05 level. Collected data were analyzed for descriptive statistics both graphically and mathematically in terms of frequency, percent, median, interquartile range, and mean and standard deviations. Differences in evaluations between materials (M1, M2, and M3) were carried out by Chi-squared test at 0.05 level. However, differences between follow-up times (T0, T1, T2, and T3) were carried out by Friedman’s test for related samples for non-parametric data. Variations caused by the three materials and follow-up times in addition to interaction between them were assessed by repeated measures ANOVA for ranked data at significance levels of 0.05. Data analysis was carried out using computer software Statistical Package for the Social Sciences SPSS (IBM-SPSSver.23.0 for MacOS). RESULTS: Results of functional properties of the three restorative materials revealed that at baseline (T0) and 3 months (T1), all cases (100%) of the three materials were clinically successful, with no significant difference between them. However, after 6 months, 58 cases (97%) of M1, 56 cases (93%) of M2, and 54 cases (90%) of M3 were clinically successful, with non-significant difference between them. Moreover, after 12 months, 55 cases (91.6%) of M1, 56 cases (93%) of M2, and 53 cases (88%) of M3 were clinically successful, with non-significant difference between them. CONCLUSION: In the purpose of restoring posterior permanent teeth in high caries risk patients, all three restorative materials demonstrated acceptable clinical performance in Class I cavities with the same success rate.